2018
DOI: 10.1007/s00266-018-1095-0
|View full text |Cite|
|
Sign up to set email alerts
|

Randomized Controlled Study Comparing Disposable Negative-Pressure Wound Therapy with Standard Care in Bilateral Breast Reduction Mammoplasty Evaluating Surgical Site Complications and Scar Quality

Abstract: BackgroundNegative pressure wound therapy (NPWT) for postsurgical incision treatment has demonstrated benefits. A prospective randomized study was developed including 32 patients who underwent bilateral breast reduction mammoplasty. Patients served as their own control and received NPWT to one breast and fixation strips to the other breast.MethodsThe primary outcome was the number of wound healing complications within 21 days when comparing NPWT treatment with fixation strips. The secondary outcome was aesthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 35 publications
5
75
0
3
Order By: Relevance
“…18 Tanaydin et al also reported that ciNPT over inframammary incisions resulted in a significant improvement over fixation strips in scar quality and appearance, assessed using the Patient Scale and Observer Scale and the Visual Analogue Scale at 42, 90, and 180 days. 19 In contrast, Svensson-Björk et al noted no significant differences between ciNPT and standard dressings for inguinal vascular surgical scars evaluated using the Patient Scar Assessment Scale, the Stony Brook Scar Evaluation, a 10-point-graded numeric ranking scale, and a modified Vancouver Scar Scale. 20 However, in this study population, the majority of surgical scars in both groups received the best possible scores indicating minimal baseline scarring, leaving little room for comparative differences.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…18 Tanaydin et al also reported that ciNPT over inframammary incisions resulted in a significant improvement over fixation strips in scar quality and appearance, assessed using the Patient Scale and Observer Scale and the Visual Analogue Scale at 42, 90, and 180 days. 19 In contrast, Svensson-Björk et al noted no significant differences between ciNPT and standard dressings for inguinal vascular surgical scars evaluated using the Patient Scar Assessment Scale, the Stony Brook Scar Evaluation, a 10-point-graded numeric ranking scale, and a modified Vancouver Scar Scale. 20 However, in this study population, the majority of surgical scars in both groups received the best possible scores indicating minimal baseline scarring, leaving little room for comparative differences.…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, Ferrando et al discovered that using ciNPT over oncological breast surgical incisions was significantly associated with better scores compared with standard dressings on three different scar assessment scales: the two physician‐evaluated Observer Scar Assessment Scale and Manchester Scar Scale; and the patient‐evaluated Patient Scar Assessment Scale . Tanaydin et al also reported that ciNPT over inframammary incisions resulted in a significant improvement over fixation strips in scar quality and appearance, assessed using the Patient Scale and Observer Scale and the Visual Analogue Scale at 42, 90, and 180 days . In contrast, Svensson‐Björk et al noted no significant differences between ciNPT and standard dressings for inguinal vascular surgical scars evaluated using the Patient Scar Assessment Scale, the Stony Brook Scar Evaluation, a 10‐point‐graded numeric ranking scale, and a modified Vancouver Scar Scale .…”
Section: Discussionmentioning
confidence: 99%
“…16 The animal studies evaluated these outcome on either postoperative day (POD) 3, 4, 5, 7, 8, 21, or 40. [16][17][18][19] Nine clinical articles reported clinical patient and observerreported outcomes, among which five RCTs, [21][22][23][24][25] three prospective comparative studies, [26][27][28] and one retrospective comparative study. 29 Clinical studies reported results after abdominoplasty, 29 circumferential thigh lift, 26 oncological breast surgery, 27 breast tissue expansion, 21 laparotomy, 25,28 vascular groin surgery, 22 reduction mammoplasty, 23 and coronary artery bypass grafting.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[16][17][18][19] Nine clinical articles reported clinical patient and observerreported outcomes, among which five RCTs, [21][22][23][24][25] three prospective comparative studies, [26][27][28] and one retrospective comparative study. 29 Clinical studies reported results after abdominoplasty, 29 circumferential thigh lift, 26 oncological breast surgery, 27 breast tissue expansion, 21 laparotomy, 25,28 vascular groin surgery, 22 reduction mammoplasty, 23 and coronary artery bypass grafting. 24 Scar scales used by the clinical studies involved the Vancouver Scar Scale (VSS), 22,29 Stony Brook Scar Evaluation Scale (SBSES), 22,26 Observer Scar Assessment Scale (OSAS), 27 Patient Scar Assessment Scale (PSAS), 22,27 Manchester Scar Scale (MSS), 27 Body Image Scale (BIS), 27 Visual Analog Scale (VAS), [21][22][23]28 Patient and Observer Scar Assessment Scale (POSAS).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The use of incisional NPWT is thus highly recommended in elderly patients, who have significant increased risk of developing SSE when compared with younger patients [61]. Other studies have concluded that incisional NPWT applied to closed surgical incisions on healthy patients after breast reduction surgery prevented postsurgical wound complications significantly [62].…”
Section: Breast Surgerymentioning
confidence: 99%